Congestion control algorithm for unreliable unicast traffic - SONG Li-hua1; CHEN Ming1; WANG Hai-tao2; XIONG Huan1 (Tongxin xuebao)
To improve performance in high bandwidth networks when trying to retain fairness, a rate-based congestion control algorithm was proposed for unreliable unicast traffic. Named rate adaptation for unreliable unicast traffic （RAUU）, this algorithm aims to preserve appropriate amount of extra packets in networks and to that end it regulates the sending rate in proportion to the difference between actual and expected extra packet quantities. It combines loss and delay signals, and made several special design choices to avoid rate control’s inherent weakness. Theoretical analysis shows that in ideal network conditions, RAUU has and will converge to its one and only equilibrium point. Simulation experiments in- dicate that RAUU can achieve similar performance as FAST and smooth throughput as TFRC while holding reasonable fairness to TCP.